Traumatic Pneumatocele - Tai-Ching Yang; Ching-Hua Huang; Jing-Wen Yu; Feng-Chi Hsieh; Yung-Feng Huang (Pediatrics and Neonatology)
Traumatic pneumatocele is a rare complication of blunt chest trauma with uncertain pathogenesis. It occurs primarily in pediatric patients and is characterized by single or multiple pulmonary cystic lesions concomitant with other type of injuries of the lung parenchyma. Herein we present a case of traumatic pneumatocele in a 3-year-old boy, together with a brief review of the literature. This rare entity should be considered in the differential diagnosis of cystic lesions complicating blunt chest trauma, especially in young adults. The disease generally has a benign and self-limiting course.